2015
DOI: 10.1099/mic.0.000004
|View full text |Cite
|
Sign up to set email alerts
|

The vintage effect overcomes the terroir effect: a three year survey on the wine yeast biodiversity in Franciacorta and Oltrepò Pavese, two northern Italian vine-growing areas

Abstract: The vintage effect overcomes the terroir effect: a three year survey on the wine yeast biodiversity in Franciacorta and Oltrepò Pavese, two northern Italian vine-growing areas analyses, the year of isolation (vintage) proved to be a factor that significantly affected the biodiversity of the yeast species, whereas the geographical site (terroir) was not. Seventy-five per cent of S. cerevisiae isolates gathered in a unique cluster at a similarity level of 82 %, while the remaining 25 % were separated into minor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
38
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 44 publications
(44 reference statements)
7
38
0
2
Order By: Relevance
“…Previous consecutive-year follow-up studies reported contrasting results concerning the possible establishment of strains as resident at a given winery (8,14). The comparison by AMOVA of samples obtained from wine estate C over a long period revealed that the variation between the most distant years (1993 and 2014) provided more differences than a comparison of different samples from the same year or from successive years (1992 and 1993 or 2013 and 2014).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Previous consecutive-year follow-up studies reported contrasting results concerning the possible establishment of strains as resident at a given winery (8,14). The comparison by AMOVA of samples obtained from wine estate C over a long period revealed that the variation between the most distant years (1993 and 2014) provided more differences than a comparison of different samples from the same year or from successive years (1992 and 1993 or 2013 and 2014).…”
Section: Discussionmentioning
confidence: 86%
“…A highly discriminating method based on 15 microsatellite markers specific to S. cerevisiae was used for molecular typing at the strain level. In comparison to previous studies based on other methods, such as PFGE, mtDNA RFLP, and inter-delta analysis (6,8,48), this S. cerevisiae ecological study used deep sampling and relied on the robustness of the microsatellite marker method (36,(49)(50)(51), performed with 15 loci as microsatellite markers and providing more sensitivity than previous studies. Multilocus microsatellite analysis allowed us to evaluate the genetic diversity of our population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This distribution is conditioned by several factors such as cultivar, vintage and climate and could be influenced by agricultural practices [15,23,24]. In addition, preliminary evidence on the association of wine microbiome and phenotype at regional level suggests a microbial contribution to regional characteristic defined as "terroir" [25,26].…”
Section: Discussionmentioning
confidence: 99%